Аналіз процесу центрифугування рицинової олії в конічній центрифузі - Повар, Ігор Юрійович; Болтянський, Борис Володимирович; Povar, Ihor; Boltianskyi, Borys (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У роботі розглянуто особливості процесу центрифугування рицинової олії в конічній фільтрувальній центрифузі. Проаналізовано умови формування вільної поверхні рідини в обертовому конічному об’ємі та визначено параметри, за яких виникає критичний профіль поверхні. Встановлено, що за перевищення критичної кутової швидкості обертання відбувається переміщення частинок олії вздовж конічної поверхні, що впливає на характер розподілу механічних домішок і ефективність очищення продукту. Також досліджено рух твердих частинок у в’язкому середовищі з урахуванням сили тяжіння, нормальної реакції поверхні, сил тертя, в’язкого опору, а також інерційних сил у неінерціальній системі відліку. На підставі отриманих залежностей охарактеризовано зони можливого перебування та руху домішок на конічній поверхні центрифуги. Результати дослідження можуть бути використані для обґрунтування раціональних режимів роботи конічних центрифуг при очищенні рицинової олії від механічних включень. /// EN: In the process of production and primary purification of castor oil, an important task is the effective removal of mechanical, colloidal and suspended impurities that deteriorate the quality of the finished product, complicate further technological operations and reduce the stability of oil storage. One of the promising methods of intensification of purification is the use of conical filtering centrifuges, in which phase separation occurs under the action of centrifugal forces. The paper considers the features of the centrifugation process of castor oil in a conical filtering centrifuge. The conditions for the formation of the free surface of the liquid in a rotating conical volume are analyzed and the parameters under which a critical surface profile occurs are determined. It was established that when the critical angular velocity of rotation is exceeded, oil particles move along the conical surface, which affects the nature of the distribution of mechanical impurities and the efficiency of product purification. The motion of solid particles in a viscous medium was also investigated, taking into account the force of gravity, the normal reaction of the surface, friction forces, viscous drag, and inertial forces in a non-inertial reference frame. Based on the obtained dependencies, the zones of possible residence and movement of impurities on the conical surface of the centrifuge were characterized. The results of the study can be used to substantiate rational operating modes of conical centrifuges when purifying castor oil from mechanical inclusions.
Analysis of the centrifugation process of retino oil in a conical centrifuge
Keywords: рицинова олія; конічна центрифуга; центрифугування; механічні домішки; фільтрування; вільна поверхня рідини; кутова швидкість; критичний режим; очищення олії; рух частинок; castor oil; conical centrifuge; centrifugation; mechanical impurities; filtration; free surface of the liquid; angular velocity; critical mode; oil purification; particle motion